Pendampingan Qiroatul Quran melalui Revitalisasi Metode Tilawati di TPQ Al Muhajirin - Ratnaningtyas, Oktavia; Asyiq , Abdullah; Aulia Syarifah, Aulia Zumrotus Syarifah; Hasanah, Nihayatul (Institut Pesantren Sunan Drajat Lamongan, Indonesia, 2025)
This community empowerment program aims to examine and strengthen the revitalization of the Tilawati curriculum at TPQ Al-Muhajirin in order to improve the quality of Qur’anic learning and students’ understanding of Islamic teachings. Using the ABCD (Asset-Based Community Development) approach, the KKN 3 Mayangan team explored the potential of the TPQ and identified a key problem: the learning process had previously focused solely on technical reading skills, resulting in limited exposure to essential Islamic subjects such as worship jurisprudence, women's jurisprudence, and monotheism. Based on these findings, the TPQ’s assets were further developed through the integration of additional Islamic materials delivered in enjoyable ways, including the use of singing to support students’ memorization. Although the revitalization faced challenges such as limited facilities, short learning hours, and varying levels of teacher readiness the process still produced positive outcomes. Students became more enthusiastic, gained a better understanding of Islamic teachings, and showed greater engagement in the learning activities. Thus, TPQ Al-Muhajirin now not only nurtures students’ Qur’anic reading skills but also strengthens their understanding and practice of Islamic values in daily life